Dentin Cross-linking Effect of Carbodiimide After 5 Years. (September 2021) - Maravic, T.; Mancuso, E.; Comba, A.; Checchi, V.; Generali, L.; Mazzitelli, C.; Josic, U.; Hass, V.; Reis, A.; Loguercio, A.D.; Tay, F.R.; Breschi, L.; et al.
Carbodiimide (EDC)–based dentin primers preserve hybrid layer (HL) integrity. However, aging >1 y has not been investigated. The present study examined whether the cross-linking effect of EDC was reflected in dentin bond strength, endogenous enzymatic activity, and the chemical profile of the HL after 5-y aging in artificial saliva. Noncarious human third molars ( N = 42) were cut to expose middle/deep coronal dentin and treated as follows: group 1, dentin etched with 35% H3 PO4, pretreated with a 0.3M aqueous EDC primer for 1 min and restored with XP Bond (Dentsply Sirona); group 2, as in group 1 but without EDC pretreatment; group 3, Clearfil SE Bond (Kuraray-Noritake) primer applied to dentin surface, followed by EDC pretreatment as in group 1 and application of bond; group 4, as in group 3 without EDC pretreatment. After composite buildup, the specimens were cut into sticks or slabs, depending on the experiment. All tests were performed at baseline (T0) and after 5 y of aging (T5) in artificial saliva at 37 °C. Microtensile bond strength (µTBS) was tested at a crosshead speed of 1 mm/min until failure. Endogenous enzymatic activity was investigated with in situ zymography. The chemical profile of HL was determined via Raman spectroscopy. Three-way analysis of variance and post hoc Tukey test were used to analyze µTBS and in situ zymography data (α = 0.05). EDC pretreatment and aging significantly influenced µTBS and in situ zymography results ( P < 0.05). Higher bond strength and lower gelatinolytic activity were identified in the EDC-treated groups at T5 ( P < 0.05), especially in the etch-and-rinse groups. Raman spectra revealed less defined amide III peaks in control specimens at T5. The EDC cross-linking effect persisted in the HL for 5 y in terms of bond strength, collagen structure preservation, and dentinal enzyme silencing.